Interpretação analítico-comportamental da inferência dedutiva nas formas silogísticas, a partir da Teoria das Molduras Relacionais - Aran Cebria, Jaume Ferran (Universidade Federal de São Carlos, 2016)
This is a theoretical paper that, given a longstanding difficulty of approaching logical reasoning from a behavioral perspective, attempts to provide an interpretation of Aristotelian syllogisms consistent with Relational Frame Theory, thus proposing a new relational frame, i.e. Relational Frames of Deductive Inference. To that end, it was analyzed, on the one hand, the account of syllogisms found in Aristotle’s Prior analytics, highlighting relevant concepts and, on the other hand, RFT literature, mainly the 2001 book by Hayes, Barnes-Holmes & Roche. In this light, we argue that Aristotelian syllogisms present the necessary features of any relational frame and also a specific pattern and specific relational cues that set it apart from other already defined relational frames. Understanding logical reasoning as operant behavior (in this case, a specific type of arbitrarily applicable relational responding) may constitute a necessary first step in developing empirical methods for the study of such an important class of behaviors.
Behavioral-analytic Interpretation of deductive inference in syllogistic forms, based on Relational Frame Theory
Keywords: Teoria das molduras relacionais; Raciocínio; Lógica; Silogismos; Relational Frame Theory; Logic; Reasoning; Syllogism; CIENCIAS HUMANAS::PSICOLOGIA